Du sollst dir kein Bildnis machen: la atribución de imágenes y su pernicioso efecto sobre la identidad de los personajes de Max Frisch - García, Yolanda (Revista de Filología Alemana, 2002)
Max Frisch is not just one of the major novelists and playwrights of Swiss Contemporary Literature. His insight of human beings, and of their passions and worries, was also exceptional. That is where the universality and timeless quality of his works and literary characters stands. His own vision of human kind, though, was not an optimistic one. In his view, people live in a lonely fight to get rid of the images that other human beings, or their own selves, cast upon their identites. Because of this attribution of images, many of his characters suffer from profound identity crisis, or either drive themselves towards their own death. These are the themes, together with the theoretical analysis of the so called «Bildnistheorie», that define the contents of this article.